How does Organizational Culture Affect Proton’s Employee Performance? - Zahra, Puteri Fatimah; Kee, Daisy Mui Hung; Aqilah, Nur; Ng, Xin Yun; Lin, Jia Yee; Vashishth, Kajal; Pandey, Rudresh; Alfadhly, Hamad; Quttainah, Majdi Anwar (AIBPM Publisher, 2020)
Organizational culture is very important especially for a group of people who work together since we believe that this is one of the main factors that contribute to the organization’s success. Therefore, the purpose of this paper is to determine how does organizational culture affects PROTON’s employee performance in this automotive industry. As we know, applying an effective organizational culture represents a special challenge but it can help PROTON in making better products over the long-term. Data were gathered by using an online survey with a sample of 210 employees. As an international corporation (PROTON), we found out that the organizational culture always gives a big impact on the business process and employee performance due to cross-cultural differences.